Transformasi Quizizz sebagai Media Pembelajaran dalam Pendidikan Agama Islam - Rizki, Aufa Fauzilla; Putra, Rido (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the transformative application of gamified platforms such as Quizizz as active learning media in Islamic Religious Education (PAI). To date, Quizizz has primarily been used as an assessment tool rather than as a medium for delivering content in a structured and progressive manner. The objective of this research is to develop a transformative model for using Quizizz as an informative, interactive, and meaningful instructional medium within the context of Islamic values. The study employed a Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate), though it was limited to the design stage. The development results show that two instructional models sequential delivery and holistic delivery were successfully designed based on the ADDIE instructional design framework and an analysis of digital-native learners’ needs. The developed media were validated by content and media experts and deemed “feasible with revisions.” The study concludes that Quizizz can be transformed into a relevant and engaging learning medium for PAI by integrating visual, interactive, and Islamic value components. The implications of this research include contributions to the literature on gamification-based digital learning in PAI and the provision of alternative interactive media aligned with the characteristics of Generation Alpha.